Periodicities, ENSO effects and trends of some South African rainfall series: an update - R. Kane (South African Journal of Science)
The precipitation data for some regions in South Africa were studied for the period 1900 - 1998. From the 11 regions examined, 8 in South Africa had maximum precipitations in the austral summer months (December, January, February, March), while 3 had maxima in autumn and winter. Annual values showed considerable year-to-year fluctuations (50% to 200% of the mean), while five-year running means showed long-term fluctuations (75% to 150% of the mean). A spectrum analysis indicated periodicities in the ranges 2 - 3 (quasi-biennial oscillation, QBO), 3 - 4 (quasi-triennial oscillation, QTO), 6 - 11, 17 - 21, 23 - 26, 32 - 35 and 55 - 66 years, some common to, and some different in different regions. The QBO and QTO accounted for a substantial fraction (30 - 50%) of the total variance. In five-year running means, the effects of QBO and QTO were suppressed considerably. The plots showed distinct peaks, but the spacings varied in a wide range, indicating that predictions based on extrapolation of single peaks are not likely to come true even for decadal averages. El Niño effects for the giant event of 1982/83 were as expected but those for 1997/98 were obscure, almost absent. Running means over 21 years did not indicate linear trends, upwards or downwards. Instead, considerable oscillations were seen, with magnitudes different in different regions (5 - 25%). On average, high values during 1915/16 decreased considerably (5 - 8%) up to 1935, oscillated upwards thereafter and recouped by 1980, but decreased considerably thereafter.